A VIEW FROM CHILE DEMOCRATIC CHANGE IN SPAIN. POLITICAL TRANSITION IN MERCURY (1975-1983) - Castellanos López, José Antonio (Revista de Historia Social y de las Mentalidades, 2024)
This article aims to become an approximation  to the idea projected in Chile about the  transition to democracy in Spain from a very  specific view: the one showed in the most  important writing media in the country, El  Mercurio de Santiago. Through a thorough  search in its opinion section and especially  the publishing section, we have outlined  an overview which attempts to describe  how this newspaper assimilated the events  which made the authoritarian dictatorial  regime of the Spanish state turn into a fully  guaranteed democracy and how newspapers  poured it onto their readers making it a  published opinion. For this purpose, we  have been trying to inquire especially into  those matters which would be used like an  excuse for their ideological position about a  double reality: the Spanish political moment  marked by political change and the juncture  in Chile, immersed in Pinochet’s dictatorship,  which was then between its continuity and its  institutionalization
Keywords: Spain; Transition; El Mercurio